EEG-based functional connectivity and executive control in patients with Parkinson's disease and freezing of gait. (May 2022) - Gérard, Morgane; Bayot, Madli; Derambure, Philippe; Dujardin, Kathy; Defebvre, Luc; Betrouni, Nacim; Delval, Arnaud
Highlights: High-resolution electroencephalography was used to explore changes over time of the networks underpinning a visual attention task in patients with Parkinson's disease and freezing of gait. During the visual attention task, patients with Parkinson's disease and freezing of gait showed impairments in executive control. The elevated theta band connectivity observed in patients with Parkinson's disease and freezing of gait during the attentional task argues in favor of the interference model. Abstract: Objective: To explore changes over time in the network specificities underpinning a visual attentional task in patients with Parkinson's disease and freezing of gait (the PD + FoG group), patients with Parkinson's disease but no FoG (PD-FoG), and healthy controls (HCs). Methods: High-resolution electroencephalography (EEG) data were acquired for 15 PD + FoG patients, 14 PD-FoG patients, and 18 HCs performing the Attention Network Test. After source localization, functional connectivity was assessed and compared by applying the dynamic phase-locking value method. Results: The PD + FoG patients showed an impairment in executive control. Furthermore, the PD + FoG patients showed abnormally high theta band connectivity (relative to HCs, and 400 to 600 ms after target presentation) in a network connecting the orbitofrontal and occipitotemporal regions. Conclusions: In PD + FoG, the greater functional connectivity between the visual network and the regions to which executive function has been attributed might indicate greater reliance on environmental features when seeking to overcome the impairment in executive control. Significance: FoG in PD involves cognitive, attentional and executive dysfunctions. Our observation of abnormally high connectivity in PD + FoG patients argues in favor of the interference model of FoG.